Thrombotic Thrombocytopenic Purpura: Diagnostic Challenges (Literature Review and Case Report) - L. Yushchyk; A. Hayduk; O. Bevz; N. Vibla; O. Didenko; A. Novosad; A. Bazylevych (Львівський клінічний вісник)
Introduction. Thrombotic thrombocytopenic purpura (TTP) is a rare but life-threatening thrombotic microangiopathy characterized by microangiopathic hemolytic anemia, thrombocytopenia, and organ ischemia due to microvascular thrombi. Its pathophysiology primarily involves a severe deficiency of the ADAMTS13 enzyme, leading to uncontrolled platelet aggregation and microthrombi formation. TTP presents with nonspecific symptoms: fatigue, petechiae, neurological disturbances, renal impairment, and fever, often mimicking other conditions. Advances in diagnosis, and targeted therapies like caplacizumab, plasma exchange, and immunosuppression have significantly reduced mortality rates from over 90.0 % to approximately 10.0-20.0 %. Still challenges remain in early diagnosis, treatment accessibility, and management.